The Experiences of a Disabled Dominatrix - Ness Cooper (Disability Studies Quarterly, 2022)
This paper uses autoethnographic data to examine how sex work and disability converge  within commercial female domination and BDSM realms. It explores the nuances around access to healthcare and even internal sex work support when disability is involved. There are few accounts of disability and professional dominatrix work and how it can affect being a successful entrepreneur. This autoethnographic account explores common questions people have regarding BDSM and being a disabled working professional. Exploring the relationships between mobility aids and sex tech, access to medical support, and giving, receiving, and mediating different forms of pain and its influence on sex work, and in particular professional dominatrix work. This paper investigates the importance of fluidity in human sexuality and how ableism can shape sexuality, including within both lifestyle and professional lives of sex workers. There’s a glimpse into how disability can affect orgasm, but also how ableism and the whorearchy can dictate that those who identify as professional domme’s should be anorgasmic and aren’t entitled to consensual sexual gratification. When exploring sex and disability, adaptive equipment needs highlighting more. Within this paper, I highlight not only purpose-built devices but sexual aids available within the BDSMsphere that can allow access to pleasure in ways that are rarely spoken about. And most importantly, I explore how navigating the healthcare system as a sex worker and pro-domme isn’t as straight cut as it should be, how activists’ messages from previous years are still being echoed, and how many sex workers, allies, and myself are still chanting the mantra for equity in healthcare for sex workers and those who practice kink. It is a much-needed look into queer crip theory and the world of professional dominatrix sex work that hasn’t been platformed before.